Wound management of ulcerated haemangioma of infancy – an audit. Issue 6 (1st March 2017) - Lokmic, Zerina; Grainger, Taya; Atapattu, Nadeeja V; Phillips, Roderic J; Penington, Anthony J
Abstract: Haemangioma of infancy, a benign tumour of blood vessels, is the most common tumour of infancy. Ulceration, the most common complication, presents a unique wound care challenge. A retrospective audit of medical records of children with haemangioma of infancy who presented to the Royal Children's Hospital, Melbourne, Australia, between January 2000 and December 2014 was undertaken with an aim to examine wound management of ulcerated haemangioma of infancy. In total, 535 hospital medical records were identified as suitable, of which 352 were randomly selected and audited, of which 84 patients had ulcerated haemangioma of infancy, and 62 were subject to wound management. Of these, 35 were successfully managed by wound dressings, 9 were not fully healed at the time of last review, and 18 were referred for surgical excision. Patients attended an average of five outpatient visits, and the average time from presentation to documented healing was 105 days. There were a total of 225 episodes of wound dressing, for which there was a documented follow‐up appointment at which healing could be assessed. Although a wide range of dressings were used, there was no clear pattern of benefit of one dressing over another. Wounds were less likely to be healed after the use of a silver‐impregnated dressing. Pain was poorly documented. Clinical assessment of whether wounds were infected was of no help in planning treatment. There is considerable variability in the management of this difficult wound group, and further prospective studies are required.